Pension reform in Ukraine: realities and requirements of the present time - Минюк, Олена Юріївна; Минюк, Дмитро Іванович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The objective of this study was to consider the main legal and regulatory framework for the regulation of pension in Ukraine to make its analysis, and to characterize it. It has been emphasized the importance of insurance companies as innovators and recognized worldwide leaders in the field of planning of retirement and savings programs. The process of pension reform in Ukraine has a complex and ambiguous character. Most experts agree on that the new reform of pension legislation cannot be regarded as a reform. Low pensions, high retirement age, the lack of means for payment of pensions do not constitute a complete list of problems facing the state and its citizens. One to protect himself and his family in case of unforeseen unpleasant situations and to have the ability to age with dignity is provided with a help from insurance companies that are recognized leaders worldwide in planning for retirement and savings programs. On the basis of researched materials the task is to analyze legal and regulatory acts concerning the regulation on provisions of pensions in Ukraine, and to highlight possible alternative directions for further improvement of pension reform in Ukraine. According to the State statistics service of Ukraine one-third of population of Ukraine are pensioners. So, for the first half of 2016 there were 12, 2 million retirees registered in the Pension Fund of Ukraine and the total expenditure of the Pension Fund is 92, 7 billion hrn., 44, 1 billion of which were financed at the expense of independent means. The Minister of social policy Pavlo Rozenko has said that Ukraine needs both pension reform and accumulative pension system to be implemented in 2017. Pension reform, which the government plans to implement in 2017, will allow to pay pensions from three different sources: solidarity system, accumulated systems and private pension insurance. There are legal organizations which the State has granted the right to deal with non-state pension insurance and they are the following: pension funds, banks, insurance companies, which are licensed for long-term savings and life insurance. The first two organizations have government guarantees, hence in case of crises they may go bankrupt. According to the Law of Ukraine "Upon insurance" insurance companies are not to be declared as a bankrupt. As foreign experience shows the leading role in this system belongs to the insurance companies, which provide financial protection for a person and his family in case of unforeseen unpleasant situations and the ability to age with dignity. In conclusion, legislative framework of Ukraine concerning regulations of pension relations based on multi-level principle that is, the finance of pensions, on the basis of the distributive and cumulative approach is fully formed. However, the analysis of fundamentals of non-state pension provision system shows that the development of private pension funds is still in its infancy. Therefore, we should learn from foreign companies such as MetLife concerning the development of the domestic insurance companies, security for pension savings which results in a dignified old age. Based on above mentioned, there is the necessity to strengthen the role of funded principles in the finance of pensions in the future. This will allow to individualize the process of accumulation of pension’s capital, to raise the standards of living of pensioners in the face of growing demographic burden on people of working age. It will also contribute to the development of financial and credit spheres of the country, to the improvement of social and labor relations, and to the formulation of the source for domestic investm.